Coryciana: The Spaces of the Collection - Roman, Luke (Renaissance and Reformation / Renaissance et Réforme)

(untitled) (Iter Press, 2022)
This article explores the relation between poetry, place, and the concept of epigram as site-specific writing in the Coryciana. Published in 1524 in an edition assembled by Blosius Palladius, this multi-author, predominantly epigrammatic collection in honour of the humanist and apostolic protonotary Johann Goritz focuses on two prime sites within the city of Renaissance Rome: Goritz’s column chapel in Sant’Agostino, and his vineyard-villa near Trajan’s Forum. The poets and editors of the Coryciana participate in a collaborative placemaking project, plotting Goritz’s new sites of piety and culture in relation to the places of Greco-Roman antiquity and the modern city. At the same time, they represent the collection itself as a textual space, imbued with the commemorative, encyclopedic, and canonizing capacities of sites and built structures in ancient and contemporary Rome.